Three-dimentional imaging in ultrasonic microscopy - Krzysztof Dynowski; Jerzy Litniewski; Andrzej Nowicki (Archives of Acoustics, 2014)
Advances in modern technology increases requirements for nondestructive characterization of material and biological properties in the μm range. The acoustic microscope presented in this paper combines C-scan and B-scan modes. The data collected during single $XY$ scan allow to present transversal and horizontal crosssections of the sample as well as real three-dimensional images of the sample interior. The system consist of several components: step motor driven mechanical scanner, transmitter/ receiver device, ADC 1 GHz board, ultrasonic heads, PC-class computer and image processing and visualization software. Image processing software is used for initial 3D image analysis of the whole image or its fragments, and for preparing it this way for vectorization. To achieve vectorization we used VTK (Visualization Tool Kit) library from Kitware Inc., which is the open source software, designed for 3D graphics and image processing. Finally iso-surface is constructed and presented as 3D scene in interactive GUI (Graphical User Interface).